New Fractal Soliton Solutions and Sensitivity Visualization for Double-Chain DNA Model - Zara Hassan; Nauman Raza; Abdel-Haleem Abdel-Aty; Mohammed Zakarya; Riaz Ur Rahman; Adeela Yasmeen; Abdisalam Hassan Muse; Emad E. Mahmoud (Journal of Function Spaces)
This article discusses dynamics of the fractal double-chain deoxyribonucleic acid model. This structure contains two long elastic homogeneous strands that serve as two polynucleotide chains of deoxyribonucleic acid molecules, bounded by an elastic membrane indicating hydrogen bonds between the base pairs of two chains. The semi-inverse variational principle and auxiliary equation method are employed to extricate soliton solutions. The collection of retrieved exact solutions includes bright, dark, periodic, and other solitons. The constraint conditions emerge naturally which ensure the presence of these solutions. Additionally, 2D and 3D graphs showing the impact of fractals on solutions are included. These plots use appropriate parameter values. Furthermore, sensitivity analysis of the considered model is also acknowledged. The outcomes reveal that these techniques are reliable, effective, and applicable to various biological systems.